Pantoea stewartii subsp. stewartii Produces an Endoglucanase That Is Required for Full Virulence in Sweet Corn - Mojtaba Mohammadi; Lindsey Burbank; M. Caroline Roper (Molecular Plant-Microbe Interactions, 2012)
Pantoea stewartii subsp. stewartii, a xylem-dwelling bacterium, is the causal agent of Stewart's wilt and blight of sweet corn. The goal of this study was to characterize the only gene in the P. stewartii subsp. stewartii genome predicted to encode an endoglucanase (EGase); this gene was designated engY. Culture supernatants from P. stewartii subsp. stewartii and Escherichia coli expressing recombinant EngY protein possessed both EGase and xylanase activities. Deletion of engY abolished EGase and xylanase activity, demonstrating that EngY appears to be the major EGase or xylanase produced by P. stewartii subsp. stewartii. Most importantly, our results show that EngY contributes to movement in the xylem and disease severity during the wilting phase of Stewart's wilt but is not required for water-soaked lesion formation.